The Testamentary and Philanthropic Value of the Settlement Bequeathed to All Saints’ Monastery by Its Founder, Saint Anthim the Iberian, Metropolitan Bishop of Wallachia - Maxim Marian Vlad, (Technium Social Sciences Journal, 2020)
Anthim the Iberian (1650 -1716) was a Georgian theologian, scholar, calligrapher, philosopher and one of the greatest ecclesiastic figures of Wallachia, led the printing press of the prince of Wallachia, and was Metropolitan of Bucharest in 1708-1715. Alongside his literary output, the cleric was the builder of the All-Saints Monastery in Bucharest - nowadays known as the Anthim Monastery in his memory. Established between 1713-1715 years, the monastery was bestowed by the founder with properties, necessary for the maintenance of the monastic congregation and the assistance of those in need. The holy metropolitan endowed it with an extremely inspired and coherent organizational status. This Settlement with a Testamentary value contains a number of 32 chapters whose content represents a veritable spiritual monument in which cult and culture, liturgy and philanthropy , homily and school, serving God and people are admirably interwoven. By his will, the Metropolitan ordained a beautiful work of social assistance from the monastery’s income. This testament may be considered a rule to live by, a guideline to the organization and management of living together both for monks and for family men, which has not lost its present interest.